2009
DOI: 10.1016/j.aca.2009.07.064
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in microdialysis sampling integrated with conventional and microanalytical systems for monitoring biological events: A review

Abstract: Microdialysis (MD) is a sampling technique that can be employed to monitor biological events both in vivo and in vitro. When it is coupled to an analytical system, microdialysis can provide near realtime information on the time-dependent concentration changes of analytes in the extracellular space or other aqueous environments. Online systems for the analysis of microdialysis samples enable fast, selective and sensitive analysis while preserving the temporal information. Analytical methods employed for online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
152
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(157 citation statements)
references
References 107 publications
2
152
0
3
Order By: Relevance
“…The number of research fields where the technique is applied are also constantly increasing, and it has been used in several animal models. 30 However, this is the first time microdialysis has been applied to monitor intervertebral discs in situ.…”
Section: Discussionmentioning
confidence: 99%
“…The number of research fields where the technique is applied are also constantly increasing, and it has been used in several animal models. 30 However, this is the first time microdialysis has been applied to monitor intervertebral discs in situ.…”
Section: Discussionmentioning
confidence: 99%
“…The reader is directed to some of the reviews on microdialysis found in the literature (92,(100)(101)(102)(103). Extensive studies have been carried out using microdialysis in the digestive system organs.…”
Section: Microdialysis Monitoringmentioning
confidence: 99%
“…Technologies such as Fluidic interconnects (Mair et al, 2006), Micro-dialysis (Nandi and Lunte, 2009), and Droplet micro-fluidics (Seemann et al, 2012) are among the methods which are currently used for optimum integration of processes performed on a chip.…”
Section: Optical Detectionmentioning
confidence: 99%